Consumer Right to Information before Purchase: Research on the Romanian Online Stores for Technical Consumer Goods - Carmen Balan (Amfiteatru Economic)
The goal of the present paper is to evaluate the status of the protection of consumer right to information before the purchase from Romanian online stores. The perspective focuses on technical consumer goods. The research pursued two major objectives. The former consisted in analysing the compliance of the online stores with the provisions of article 6 paragraph 1 of the Directive 2011/83/EU on consumer rights, relative to the information provided to potential buyers before the purchase. The latter was to identify the consumer awareness of the rights stipulated by article 6 of the directive, as well as to study the opinions of consumers relative to the information that online stores are compelled to supply before purchase. The first objective was accomplished by applying the content analysis method to the information available on the Web for a sample of 100 online stores. The second objective was achieved through the survey method on a sample of 351 persons from the 25 to 34 age group, residing in Bucharest. Compared to other studies, the major contributions of the present research approach are the following: the investigation of an extensive sample of online stores; the wider range of products; the focus on both online stores and consumers. The results show that improvements are needed in the level of compliance and in the consumer awareness of own rights.